Motivation among contract workers - A field study at the University of M’sila - Lahmidi, Adel; Djaballah, Taieb (Al-Jamie Journal In Psychological Studies and Educational Sciences, 2024)
The study aimed to address the topic of motivation among workers as well as the contract work system in the field of human resources, as human resources are considered the vital nerve and the beating heart of the institution and one of the most important and influential inputs on the organization or institution, as the human element is the basis of productive activity, which is what made it receive great attention from thinkers and researchers in order to use the latest systems in work, as it is considered one of the most important topics in the field of management in general and the field of work in particular, as it entails a set of consequences, including the performance of workers, especially if it is related to the motivation of individuals. If their work system is based on contracting or continuity, it has a great impact in stimulating their motivations and improving their performance towards work and raising their morale and other indicators with a positive connotation, and the source of this interest lies in the fact that the study of motivations constitutes the explanatory aspect of the behavior of individuals, and since knowledge of the needs of individuals and their goals that they want to achieve enables the institution to find ways to adapt the behavior of individuals to the goals they aspire to, while if the work system is based on contracting, individuals become in Confusion about their future career in the institution, which is reflected in their level of professional stability and job security, as well as their organizational commitment and loyalty to their institutions, which led us to study this topic by knowing the level of motivation of contract workers at the University of M'sila, where the study community consisted of administrative workers at the university, and the study sample included (63) individuals. Through the application of appropriate statistical methods, the results of the study showed that: The level of motivation for work is average among the administrative employee at the university - There are statistically significant differences between the dimensions of motivation for work among the administrative employee - There are no statistically significant differences between administrative employees in the dimensions of work motivation according to the gender variable.